Platform Penjualan Bibit Ikan Gurame Berbasis Web dengan Sistem Pre-Order dan Monitoring Pertumbuhan - Hakim, Alvin Rainaldy; Habiba, Curie (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2026)
Giant gourami hatchery businesses in Jepara Regency face three interrelated structural problems: entirely conventional marketing, the absence of a planned ordering mechanism that aligns production cycles with demand, and the unavailability of objective seed-quality evidence that prospective buyers can verify. This community service programme aimed to design, implement, and evaluate a web-based giant gourami fry sales platform integrating a pre-order system with a growth monitoring module for the partner Jual Bibit Ikan Gurame Jepara in Sengonbugel Village, Mayong District. Implementation employed a Participatory Action Research approach combined with an evolutionary prototyping software development cycle across six stages over six months, accompanied by four structured training sessions. Evaluation was conducted multidimensionally through black-box functional testing referring to ISO/IEC 25010, usability measurement using the System Usability Scale, assessment of partner capacity improvement using normalised N-Gain, and analysis of business performance before and after the intervention. The results show that the platform, comprising seven modules and 42 functions, passed all functional test scenarios, obtained a usability score of 82.5 (excellent category, grade B), and improved the partner's digital capacity with an N-Gain of 0.74 (high category). The partner's empowerment level rose from level 1 to level 3, market reach expanded from one regency to six regencies, and partner income increased by 34.6% during the first three months after implementation. In-depth analysis indicates that the greatest contribution came not from transactional functions but from growth-data transparency that reduced information asymmetry between hatchery operators and grow-out farmers.